COMMUNICATION SKILLS AT JOB INTERVIEW: PEDAGOGICAL INSIGHT INTO THE PROBLEM - J. Ageeva (Образование и наука)
The aim of the study is to justify the need of teaching students how to use communicative skills in foreign language during the job interview; to demonstrate how to form the corresponding verbal competences based on the analysis of the certain communicative situation.Methods. The complex of complementary research methods are used in order to achieve the set goal: theoretical methods – analysis, synthesis, generalization of research papers; empirical methods – discourse-analysis of institutional communication; methods of data collection and storage; experimental methods – experimental learning, implementation.Results and scientific novelty. It is shown how to build up pupils’ competence of speech behavior during business dialogue, proceeding from a communicative situation. For the first time the job interview was described from the communicative point of view (strategic goals and verbal behavior of both communicators) based on the recordings of real job interviews.Practical significance. The study results presented in the paper may be used in direct teaching communicative skills at the job interview, in theoretical courses (delivering lectures on cross-cultural education, teaching foreign languages, the language of the specialty, etc.).